Near infrared estimation of concentration of ginsenosides in Asian ginseng. Issue 2 (April 2019) - Inagaki, Tetsuya; Katayama, Norihisa; Cho, Rae-Kwang; Chen, Xijun; Tsuchikawa, Satoru
In this study, the feasibility of near infrared reflectance spectroscopy for the quality evaluation of the main bioactive compounds, ginsenosides, in Panax ginseng was examined. Second derivative NIR spectra of standard reagents of ginsenoside Rg1, Re, Rb1, Rc, Rb2 and Rd were used for analysis. Characteristic bands were observed at around 5250 cm −1 in the spectra of ginsenoside Rg1 group (including Rg1 and Re); however, this was not to be observed on the spectra of ginsenoside Rb1 group (including Rb1, Rc, Rb2 and Rd). PLS regression models were constructed of air-dry ginseng powder samples and ginsenoside content in ginsengs was determined by HPLC methods. The calibration models covered various types of ginseng (white ginseng, red ginseng and bleached ginseng) from various cultivated areas (Japan, China and Korea) and were well established for each kind of ginsenoside. It was shown that NIR spectroscopy can be used for the accurate prediction of ginsenoside.